(untitled) (Archives of Clinical Psychiatry, 2009)
BACKGROUND: Injuries due to road traffic accidents are a major public health problem as well as one of the main causes of death among young males aged 15 to 44 years. OBJECTIVES: This paper reviews the relation between impulsiveness and risk driving behavior and between impulsiveness and traffic accidents. METHODS: Bibliographic review. Sources: MedLine (1966 to 2006), Cochrane databases, LILACS, Desastres, PsycINFO and CAPES theses archive. RESULTS: In total, 11 original studies (n=3806). Association between impulsiveness and speeding for the thrill (02 articles), impulsiveness and driver violations (03 articles) and impulsiveness traffic road accidents (03 articles). CONCLUSIONS: The impulsiveness is associated to the risky driving behavior, "run for thrill" and "traffic violations". The association between impulsiveness and accident proness is controversal.